Pengaruh Ekonomi Digital terhadap Model Bisnis Tradisional di Sektor Industri Kreatif - Sihotang, Widodo (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This study aims to analyze the influence of the digital economy on changes in traditional business models in the creative industry sector. In the era of rapid digitalization, many creative industry players are shifting from traditional business models that rely on physical distribution to digital-based business models. Through a qualitative approach, this study collected data through in-depth interviews with creative industry players and related literature studies. The results show that the adoption of digital technology has expanded market reach and improved product distribution efficiency through digital platforms such as Spotify, YouTube, and Instagram. Business model transformation also includes a shift from physical marketing to digital marketing, which allows for more direct and personalized interactions with consumers. However, the challenges of global competition and the need to continuously innovate in marketing and production of works are major obstacles. This research concludes that creative industry players who are able to adapt and innovate with digital technology will be better able to survive and thrive in an increasingly competitive global market. Suggestions include developing a more integrated digital strategy and increasing engagement with consumers to maintain competitiveness.